Relevansi Nilai Pendidikan Islam dan Tasawuf dalam Suluk Bismillah bagi Abdi Dalem Padepokan Jabalahad Keraton Surakarta - Ririn Perdananingrum; A. Dardiri Hasyim (Fahima, 2022)
This study aims to find out: 1) Islamic Education Values in Suluk Bismillah for Abdi Dalem in Padepokan Jabalahad Keraton Surakarta Hadiningrat, 2) Sufism Teachings in Suluk Bismillah for Abdi Dalem in Padepokan Jabalahad Keraton Surakarta Hadiningrat, 3) Relevance of Islamic Education Values and Sufism Teachings in Suluk Bismillah for Abdi Dalem in Padepokan Jabalahad Keraton Surakarta Hadiningrat. This research is library research, namely collecting research data from the literature and making the "text world" the main object of analysis. In this case the author analyzes the text of Suluk Bismillah for Abdi Dalem in Padepokan Jabalahad Keraton Surakarta Hadiningrat. In addition, the author also made observations, interviews, and documentation with Abdi Dalem at Padepokan Jabalahad Keraton Surakarta Hadiningrat. The data collection method used in this writing is hermeneutic studies, interviews, and documentation. The results of the study can be concluded that: (1) The values of Islamic Education in Suluk Bismillah for Abdi Dalem in Padepokan Jabalahad Keraton Surakarta Hadiningrat include: a) The values of relationship with the Creator, b) The relationship of man with man (society) is the value of ta'awun (help), the value of ' adalah (justice) and 'ihsan (doing more or best towards others), c) Human relationship with world life is the value of ibtila (test),  d) Man's relationship with the universe is the value of taskhir (utilization and management) and the value of learning, e) The relationship of man with the afterlife is the value of mas'uliyah (accountability) and jaza' (retribution), f) The relationship of man with science is the value of fard (individual obligation). (2) The teachings of Suawuf in Suluk Bismillah for Courtiers in Padepokan Jabalahad Keraton Surakarta Hadiningrat include: a) Alam Ahadiyah, b) Alam Wahdah, c) Alam Wahidiyah, d) Alam Arwah, e) Alam Mitsal, f) Alam Ajsam, g) Alam Insan Kamil (3) Relevance of Islamic Educational Values and Sufism Teachings in Suluk Bismillah for Courtiers in Padepokan Jabalahad Keraton Surakarta Hadiningrat,  includes: Suluk Bismillah is used as a means of drawing closer to the Creator, affirming our position as human beings in the position of insan kamil, then to reach insan kamil or return perfectly must meet two conditions, namely khalifatullah fil ard and obedient abdullah.